1999
DOI: 10.1002/(sici)1097-4628(19990829)73:9<1655::aid-app6>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The interrelation between morphology, resistivity, and flow properties of carbon black-containing HIPS/EVA blends

Abstract: Immiscible polymer blends based on high-impact polystyrene/ethylene vinyl acetate (HIPS/EVA) are interesting host multiphase systems for the incorporation of low concentrations of carbon black (CB). The conductive filler CB tends to accumulate preferentially within the EVA phase, forming segregated structures, and thus conductivity of the blends is only obtained when double percolation is realized. Material properties such as surface tension and crystallinity of the CB-containing polymer are found to influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
3
26
2
Order By: Relevance
“…The experimental results indicate that the percolation threshold lies in about 3% and the percolation region is from 3 to 5%. In evidence, the percolation value of the PVDF=PVDF-g-CB conductive film in this study is much lower than that of many other polymer composites [32,33] .…”
Section: Percolation Behaviorcontrasting
confidence: 56%
“…The experimental results indicate that the percolation threshold lies in about 3% and the percolation region is from 3 to 5%. In evidence, the percolation value of the PVDF=PVDF-g-CB conductive film in this study is much lower than that of many other polymer composites [32,33] .…”
Section: Percolation Behaviorcontrasting
confidence: 56%
“…The percolation threshold of the material lay in about 3 wt % and the percolation region was among 3~5 wt %, much lower than that of many other polymer composites (see Fig. 3) [18,19]. Figure 4 suggested that after heat-treatments the initial resistance values reduced gradually with the prolonged annealing time at 40°C.…”
mentioning
confidence: 84%
“…In this study polymer melt viscosity was adjusted by temperature and shear rate. [30] Independent of the particular effect under consideration, the critical question for each composite is whether the morphology is governed by thermodynamics or kinetics. Soares et al report that the conductivity of styrene±butadiene and PS systems is significantly impacted by molding time, temperature, and pressure.…”
Section: Conductive Literature On Single-phase Polyolefin Compositesmentioning
confidence: 99%